Comment on He et al., VATS bronchial sleeve resection - Jones, David R. (Journal of Thoracic Disease, 2014)
Video-assisted thoracic surgery (VATS) lobectomy has become the standard of care for resection of early-stage non-small cell lung cancer. The results of nearly all studies to date suggest that patients return to work sooner, have less postoperative pain, and are able to initiate and complete adjuvant therapies more expeditiously, compared with open thoracotomy (1,2). It remains an open question how often VATS can be routinely applied for several situations, including postinduction anatomic resections, bronchial sleeve resections, and pulmonary arterioplasties. In this paper from the First Affiliated Hospital of Guangzhou Medical University, Dr. He and colleagues retrospectively report their experience with VATS bronchial sleeve resection in 20 highly selected patients. No patient who needed a pulmonary arterioplasty was included, and only one patient had induction therapy. During the study period of 22 months, VATS bronchial sleeve resection composed 41% of the total number of sleeve resections (n=49) performed. The majority of sleeve resections were of the right upper lobe (n=11, 55%), with the remaining lobes having at least one sleeve resection.